Integrating English, Arabic, ICT skills, and Tahfidz in An Islamic School Curriculum: An Intercultural Perspective - Nashruddin, Wakhid; Gazali, Erfan; Mahdi, Rijal; Muhammad, Hafid Nur; Daeworsnung, Abdulrazaq (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The aim of the study is to hear teachers’ voices in relation to curriculum development in an Islamic school in Pattani, Thailand. With their experiences as intellectuals and practitioners of teaching in Islamic schools, curriculum development cannot neglect them, as has been happened in the past. Teachers were not involved in the curriculum development, and let it be decided by politicians. With many aspects occur in the global life change, come up an idea to integrate English, Arabic, ICT skills, and tahfidz in an Islamic school curriculum in Thailand. The study employed qualitative research using a questionnaire with a combination of closed- and open-ended items. 14 teachers participated in the study and filled out the questionnaire. The open-ended items’ results were calculated using percentage, and the open-ended items’ responses were analyzed using Christensen’s theory of the job-to-be-done. The result shows that teachers’ perception was negative, indicating that their involvement in the curriculum was not accommodated. However, in the context of curriculum development, teachers actually know the job to be done, what experiences needed so the job to-be-done, and has conducted limited actions or practices for the job-to-be-done. This study implies that teachers’ voices should be heard more than before, especially in the context of curriculum development. With the limitation of the study, such as numbers of participants participated, this study can be used as a basis for further discussion and curriculum empowerment using intercultural perspective for the development of school curriculum, especially the curriculum of Islamic schools.